Analysis of Students' Understanding of Adolescent Reproductive Health to Grow Health Care Behavior in Biology Learning - Intan Nissa Fatimah; Indah Ayu Lestari; Aqidatul Nissa; Eva Fitriyana; Sulistiana Sari; Irvan Maulana Fikri (Journal of Educational Analytics, 2022)
One of the problems of adolescents who are not aware of the importance of reproductive health can certainly result in the application of bad health behaviors, for example unwanted pregnancies, abortions, increased sexually transmitted diseases, and of course this can affect adolescents' readiness for the future. This study aims to find out about students' understanding related to adolescent reproductive health in order to foster health care behavior in biology learning. The approach used in this study is a qualitative approach. The population of this research is high school teenagers in Kudus Regency. Meanwhile, the determination of the number of samples in this study was through a random sampling technique, because when taking samples from members of the population it was done randomly. The data collection technique in this study was to use a questionnaire (questionnaire), as well as interviews with one of the teenage students. The data analysis technique used is interactive analysis which covers 3 parts namely, data reduction, presentation, and drawing conclusions.